The Effect of Liquidity and Capital Structure on Profitability in Retail Sub Sector Companies on the Indonesia Stock Exchange in 2018-2021 - Clara Arisany Lasol; Steven Siaila; Restia Christianty (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the effect of liquidity and capital structure and firm size on profitability in retail sub-sector companies whose shares are traded on the Indonesia Stock Exchange in 2018-2021. The sample was taken with a purposive sampling technique so as to get a sample of 10 companies studied during 2018-2021. The analysis method used is panel data analysis with the Multiple Linear Regression Analysis Method. Basd on the results of this study, partially the liquidity variable current ratio (CR) has a positive and significant effect, the capital structure debt to equity ratio (DER) has a negative but insignificant Simultaneous test results CR, DER together have a positive effect on the profitability of retail subsector companies on the Indonesia Stock Exchange in 2018-2021.